Analyzing Conflict Freedom for Multi-threaded Programs With Time Annotations - Chen, Jingshu; Duflot, Marie; Merz, Stephan (Electronic Communications of the EASST, 2014)
Avoiding access conflicts is a major challenge in the design of multi-threaded programs. In the context of real-time systems, the absence of conflicts can be guaranteed by ensuring that no two potentially conflicting accesses are ever scheduled concurrently. In this paper, we analyze programs that carry time annotations specifying the time for executing each statement. We propose a technique for verifying that a multi-threaded program with time annotations is free of access conflicts. In particular, we generate constraints that reflect the possible schedules for executing the program and the required properties. We then invoke an SMT solver in order to verify that no execution gives rise to concurrent conflicting accesses. Otherwise, we obtain a trace that exhibits the access conflict.